Radar systems, peak detection and tracking - Kolawole, Michael O. (Newnes, 2002)
As well as being fully up-to-date, this book provides wider subject coverage than many other radar books. The inclusion of a chapter on Skywave Radar, and full consideration of HF / OTH issues makes this book especially relevant for communications engineers and the defence sector. * Explains key theory and mathematics from square one, using case studies where relevant * Designed so that mathematical sections can be skipped with no loss of continuity by those needing only a qualitative understanding * Theoretical content, presented alongside applications, and working examples, make the book suitable to students or others new to the subject as well as a professional reference.
Keywords: Radar.; elektronické knihy; electronic books